Eksilanti, prišleki in kozmopoliti: Polić Kamov, Kovačič, Tomizza in Albahari skozi meje, jezike in kulture - Kinkela, Eugen (Slavistična revija, 2020)
This article analyses the cases of four writers: Janko Polić Kamov, Lojze Kovačič, Fulvio Tomizza, and David Albahari. All of them, each in his own way, write about their personal experiences of not belonging within the linguistic, cultural, and political borders of their times and space. In spite of their highly personal approaches their artistic visions have a lot in common.
Keywords: Albahari, David; cosmopolitism; književnost; Kovačič, Lojze; kozmopolitizem; literature; nepripadanje; nomadism; nomadizem; not belonging; Polić, Janko; Tomizza, Fulvio